Pressure–impulse response of semi-rigidly connected steel plates under blast loading. Issue 1 (March 2017) - Lin, Xiaoshan; Ashraf, Mahmud
In this study, a three-dimensional finite element model is developed to investigate the pressure–impulse response of the steel plates with semi-rigid connections under blast loads. The strain rate effect on the material properties is considered, and a number of spring elements are used for simulating the plate to support connections. Once verified, the developed finite element model is then used to investigate the effects of a series of parameters on the blast resistance and energy absorption capability of the steel plates, including the effects of connection rigidity, plate thickness, impulse loading and the shape of corrugation.